SC4 Developing a modular programme for doctors returning to training in Thames Valley. (3rd November 2019) - Greig, Paul; Higham, Helen; O'Hara, Tina; Duncan, Sandra; Jacques, Andrew; Davison, Marc
Abstract : Background: At any moment approximately one in ten doctors in training are taking approved time out of their programme. Returning to training after a break from clinical work can be daunting, with many trainees expressing anxiety about readjusting to the workplace. Recognising this, the Department of Health allocated £10 million nationally to Health Education England to support doctors as they return to training. Summary of education programme: The educational programme in Thames Valley was developed collaboratively by a network of educationalists across our region. Trainees themselves had input into the design of the programme, and the educational materials provided. We created a modular suite of activities incorporating technical and non-technical skills training orientated towards medicine, surgery, anaesthetics, critical care, paediatrics, and retrieval. Sessions cater to various learning styles, incorporating tutorials, skills workshops, and high-fidelity simulation. Sessions run quarterly throughout the year. Summary of results: To date we have trained 71 doctors; feedback has been excellent. Trainees particularly value the tailored range of educational activities provided, and 93% would recommend the programme to colleagues. We also collect data from trainees after they have returned to work. Thus far only 5 trainees have returned to work and provided us with feedback. They reported benefit from the training, particularly highlighting the practical aspects such as emergency drills and simulation. Discussion: The training is valued by our participants, but barriers to delivery exist. The main challenge has been identifying eligible trainees to invite. Our most successful publicity has been trainee-driven via social media, as it has been difficult to compile comprehensive contact lists from centrally held data. New communication strategies are in place via Training Programme Directors and Educational Supervisors to better advertise these resources. Some participants also reported that they found it difficult to arrange childcare to cover these sessions, and Health-education Thames Valley have generously provided additional funding to provide crèches at some modules. This has been highly popular with those returning from maternity leave and this has been a decisive factor in some trainees' attendance. Conclusion: Targeted, bespoke training designed for returning trainees is a national priority, and highly valued by trainees. Flexibility in provision is essential to cater for the varying needs of trainees as they return. Recommendations: Modular training is popular and valued by trainees Communication and targeted publicity is essential Addressing barriers such as childcare can provide a significant boost to recruitment